Alumni from the Undergraduate Rural Education: who are they, where are they and how do they evaluate their training? (Olhar de Professor, 2022)
This paper analyzed part of the data from a survey with alumni from the Undergraduate Rural Education Program (LeCampo) at Minas Gerais University (local acronym FaE/UFMG).  It is about their performance as educators in the rural. The investigation is anchored in the need to understand the performance of alumni, considering the purposes of Rural Education for this degree in Brazil. The research is a case study, with a qualitative approach, critically and dialectically analyzes data obtained in an online questionnaire and uses national literature to discuss the data. Results show to the insertion of the alumni in the teaching and permanence of link with rural social moviments. Regarding teaching, the percentage of alumni working in rural schools is significant, with the capacity to contribute to their transformation and qualification in this space.
Keywords: Undergraduate Course in Rural Education. Alumni. Rural Educators.